(untitled) (African Journal of Biomedical Research, 2022)
In this study, the effects of carbamazepine on hippocampal histomorphology, acetylcholinesterase activity, and glutamate concentration in adult male Wistar rats were investigated. Healthy Wistar rats of the male sex weighing between 200g-250g assigned randomly into 4 groups (n= 5) were utilized for this study. Group A received 2 mLs/Kg of distilled water, groups B, C and D received 160mg/kg, 120mg/kg, and 80mg/kg of carbamazepine. Carbamazepine was supplemented in rat chow for the study span of four weeks. The whole brain was harvested the following sacrifice fixed in 10% Neutral Buffered Formalin (NBF) and stained in H&E and Cresyl violet for hippocampal histomorphology and Nissl substances evaluation. Hippocampal Acetylcholinesterase (AChE) activity and concentration of glutamate were biochemically determined. Data obtained was analyzed using one-way ANOVA followed by Student Newman Keul posthoc test. A value of p<0.05 was considered significant. Results revealed statistically significant decrease in weight change across all experimental groups (F = 6.820, p = 0.0036). Relative brain weight (F = 0.9048, P = 0.4803), activities of glutamate ((F= 0.4545, p = 0.7214) and AChE (F= 0.4128, p = 0.7484) were not significantly different across group in comparison to control. Group B which received the highest dose of CBZ (160mg/kg) showed widespread pyramidal and granule neuronal degeneration, while group C also showed mild degenerative changes in comparison to the control Based on the data from our study, carbamazepine exerted neuronal degenerating tendencies on the hippocampus is in a dose-dependent manner. This in turn will affect hippocampal-related functions